Exploiting the impact of the secretome of MSCs isolated from different tissue sources on neuronal differentiation and axonal growth - Silva, Rita Catarina Assunção Ribeiro (2018)
Cell transplantation using Mesenchymal stem cell (MSC) secretome have recently been presented as a possible free-based therapy for CNS related disorders. MSC secretome is rich in several bio-factors that act synergically towards the repair of damaged tissues, thus making it an ideal candidate for regenerative applications. Great effort is currently being made to map the molecules that compose the MSC secretome. Previous proteomic characterization of the secretome (in the form of conditioned media - CM) of MSCs derived from adipose tissue (ASC), bone-marrow (BMSC) and umbilical cord (HUCPVC) was performed by our group, where proteins relevant for neuroprotection, neurogenic, neurodifferentiation, axon guidance and growth functions were identified. Moreover, we have found significant differences among the expression of several molecules, which may indicate that their therapeutic outcome might be distinct. Having this in mind, in the present study, the neuroregulatory potential of ASC, BMSC and HUCPVC CM in promoting neurodifferentiation and axonal outgrowth was tested in vitro, using human telencephalon neuroprogenitor cells and dorsal root ganglion explants, respectively. The CM from the three MSC populations induced neuronal differentiation from human neural progenitor cells, as well as neurite outgrowth from dorsal root ganglion explants. Moreover, all the MSC populations promoted the same extent of neurodifferentiation, while ASC CM demonstrated higher potential in promoting axonal growth.